Social Studies Learning Social Justice Issues In Education And Management Of Students Development In Nigeria - Abdullahi, Nimota Jibola Kadir (Universitas Pendidikan Indonesia (UPI), 2021)
ABSTRACT One this study examined the relationship between equal opportunity to learning, provision of basic needs, teacher preparation of lesson and students’ development in Kwara State, Nigeria. Proportional sampling procedure was used to select participants from sample public senior secondary schools in Kwara State, Nigeria. Questionnaire titles “Social Justice and Management of Students’ Development Questionnaire (SJMSDQ) was used to gather data and analysed with the use of quantitative statistics tools. The outcomes shown that there is no significant difference between equal opportunity to learning, provision of basic needs, teacher preparation and management of students’ development in Nigeria. The researcher recommended that educational managers should provide equal access to schooling for all learners irrespective of their age so as to encourage students empathize with others and develop the skill of critical thinking. Also, government should ensure adequate provision of basic needs to facilitate effective teaching and learning in order to make students think effectively and develop the skills for relevant judgement. Subsequently, government should encourage teachers to improve on the effective preparation of lesson so as to help in the growth and development of the students’ cognitive, affective and psychomotor domains as well as helps to promote the overall personality development of the students.